(untitled) (Revista Contexto & Educação, 2022)
There is general agreement that the level of schooling is the main factor that determines the wage income discrepancies between individuals. However, there is no consensus regarding the explanatory power of these different levels of schooling. In this way, the purpose is to verify if the explanatory power of the variable degree of instruction on the remuneration increases in the proportion in which the years of study are increased, indicating therefore some levels where other variables would influence more the remuneration than the level of schooling. The results indicate that for the lower education groups the explanatory power of the years of study on their remuneration is statistically significant, but it is lower than the explanatory power on the group with the highest level of schooling, indicating that for the lower education groups there are other factors which have a greater impact on the individual’s remuneration.